Finding Best Semantic Relatedness Functions For Schema Matchers - Emadzadeh, Ehsan (2010)
Data management is one of todays interesting problem to solve. Data sets grow rapidly and techniques which process them should grow as well. Mining proper knowledge from vast data source became challenging task. To achieve reliable, accurate and integrate definition data sources. for this purpose all different data structure definitions (schema) should be matched together.